AI for Students in the Age of Digitalization - Andrean Viky Orlando; Mehdi Mahda Fiqy; Fedly Fernand Latuperisa; Muhammad Helmi Mustofa (Immortalis Journal of Interdisciplinary Studies, 2025)
The digital era has brought artificial intelligence (AI) as a significant innovation that is transforming the way students learn in higher educa-tion. This study aims to examine the benefits, challenges, and strategies for utilizing AI in higher education through a systematic literature review using the PRISMA method. The analysis results show that AI can improve the accessibility and quality of learning through person-alized materials, automated evaluation, and technology-based interactive learning support such as chatbots, virtual assistants, and augmented reality. The implementation of AI also encourages better time management, increases student motivation to learn, conceptual understanding, and problem-solving skills. However, the use of AI poses serious challenges such as the risk of dependency, decreased critical thinking skills, data privacy issues, and the potential for plagiarism. Therefore, a balanced approach is needed between the use of technology and the strengthening of ethical values, including the development of regulations, increasing digital literacy, and training educators to optimize the wise use of AI. The conclusion of this study confirms that AI, when properly integrated, not only strengthens the effectiveness of learning but also prepares students to become adaptive, creative, and ethical graduates in facing the demands of the digital era.